2009
DOI: 10.1080/09513590802404013
|View full text |Cite
|
Sign up to set email alerts
|

Triggering with HCG or GnRH agonist in GnRH antagonist treated oocyte donation cycles: a randomised clinical trial

Abstract: The findings of our RCT suggest that donor and recipient outcome are comparable in OD cycles triggered with hCG or a GnRH agonist. Furthermore, the risk of OHSS seems to be reduced considerably, therefore the combination of a GnRH antagonist protocol with GnRH agonist triggering constitutes a safe treatment option for egg-donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 29 publications
2
50
0
4
Order By: Relevance
“…Two randomized controlled trials with high-risk IVF patients (1,2) confirmed the absence of moderate/severe OHSS and implantation rates seemed not to be affected by the use of vigorous luteal support. In the context of oocyte donation, the reduction in OHSS incidence was demonstrated both by retrospective series (3)(4)(5) as well as randomized clinical trials (6,7). Our group has published the largest experience (4,7) to date with GnRH-agonist triggered oocyte donor cycles.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Two randomized controlled trials with high-risk IVF patients (1,2) confirmed the absence of moderate/severe OHSS and implantation rates seemed not to be affected by the use of vigorous luteal support. In the context of oocyte donation, the reduction in OHSS incidence was demonstrated both by retrospective series (3)(4)(5) as well as randomized clinical trials (6,7). Our group has published the largest experience (4,7) to date with GnRH-agonist triggered oocyte donor cycles.…”
mentioning
confidence: 95%
“…In the context of oocyte donation, the reduction in OHSS incidence was demonstrated both by retrospective series (3)(4)(5) as well as randomized clinical trials (6,7). Our group has published the largest experience (4,7) to date with GnRH-agonist triggered oocyte donor cycles. This strategy contributed in large part to the overall safety of our egg donation program, which is predominantly based on the use of the GnRH antagonist stimulation protocol (8).…”
mentioning
confidence: 95%
“…After the demonstration of the partial inhibition of ovarian VEGF receptor 2 (VEGFR-2) phosphorylation levels by the dopamine agonist cabergoline in an animal model [35] and its consequent reversion of VEGFR-2 vascular permeability Cabergoline inhibits partially the VEGF receptor 2 phosphorylation levels and associated vascular permeability without affecting luteal angiogenesis [35] Reduction on the 'early'(within the first 9 days after hCG) onset of OHSS [36] Even using cabergoline, the OHSS incidence may be as high as 10.8% [36] Non-steroidal antiinflammatory A large RCT demonstrated that low dose aspirin was associated with reduction in the OHSS incidence (0.25% vs. 8.4%) in a high-risk group with similar pregnancy rates [37] Meloxican was capable of reducing the OHSS associated ovarian weight and expression of VEGF in an animal model [38] GnRH antagonist protocol This regimen is associated with a significant reduction in OHSS (Odds Ratio=0.60) as well as with fewer interventions to prevent OHSS (OR=0.43) However a slight reduction in pregnancy rates was also observed (OR=0.83) [39] Replacement of hCG A single dose of recombinant LH was safer than hCG and was effective in inducing follicular maturation The dosage of 15,000-30,000 IU is still too expensive [42] Using a GnRH agonist to induce final oocyte maturation, no cases of moderate/severe OHSS were observed in 1,152 cycles of oocyte donation against 14 cases in 1,137 cases who received hCG [43,44]. This requires the use of GnRH antagonist protocol.…”
Section: Dopamine Agonist Administrationmentioning
confidence: 99%
“…Replacing hCG with GnRH agonists was shown to be financially acceptable, with good pregnancy rates and a dramatic decrease in severe and moderate OHSS [43][44][45].…”
Section: Reducing Hcg Dosagementioning
confidence: 99%
See 1 more Smart Citation